Motive for Watching Da'wah Content on Instagram Account Habib Husein Ja'far Al-Hadar @husein_hadar (Analysis of Uses and Gratification Theory) - Yusup, Ilham Maulana; Marzuqi, Muhammad Ganda; Fano, Abiyyu Alfio; Zuhriyah, Luluk Fikri (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
In the current era of information society, audiences are increasingly active and free to choose media and content that suits their wishes and can no longer be dictated by one media at a time to meet their needs. This study aims to determine Habib Ja'far's Instagram followers' motives for deciding to watch the content presented by this famous da'i, who also doubles as a da'wah influencer. This research uses descriptive qualitative research methods with the theory used in this research is Uses and Gratifications Theory. Based on the results of this study, the motive for watching Habib Ja'far da'wah's content on the @husein_hadar Instagram account is based on five elements of the type of needs satisfied by the media according to Katz, et al in Uses & Gratification Theory, namely: Personal Integrative Needs, Social Integrative Needs, Cognitive Needs, Affective Needs, and Escapist Needs. one of the classifications of audience needs and satisfaction according to McQuail, He identified several ways to classify audience needs and satisfaction, one of which is personal relationship, which occurs when people use the media instead of their friends.